ANALYZING THE LEVEL OF SERVICE AT ANJUK LADANG TERMINAL, NGANJUK REGENCY BY IMPORTANCE PERFORMANCE ANALYSIS (IPA) METHOD - Kurnia Hadi Putra; Ita Suhermin Ingsih; Ikhsan Dwi Mukharom (Journal Innovation of Civil Engineering (JICE), 2022)
A bus terminal is an infrastructure for road transportation to drop off and pick up passengers. Anjuk Ladang Terminal in Nganjuk Regency, which is a busy terminal, requires services that can provide comfort and safety for passengers.Therefore, this research was aimed at investigating the level of service of the Anjuk Ladang bus terminal and determining the level of passenger satisfaction toword terminal service through questionnaires employing the ImportancePerformance Analysis method. Furthermore, it was intended to investigate the suitability of the facilities at the Anjuk Ladang terminal based on the Regulation of the Regulation of the minister of Transportation Number PM 132 in 2015.The result of analyzing the user of Anjuk Ladang Terminal service indicated that they where quite satisfied with the interior display, environmental cleanliness, courtesy of officers in aserving customers,and terminal officer honesty. Meanwhile, quadrant I of the Cartesian diagram demonstrated limitations in term of customer care from the staff, cleanliness in the toilet and passenger waiting rooms, as well as security at the terminal. In conclusion, Anjuk Ladang Terminal must improve the quality of services included in quadrant I. However, the facolity’s suitability has complied with the Regulation of the Minister of Transportation Number PM 132 in 2015.